Indirect Relationship between Leadership Style, Organisational Commitment and Academic Employee Performance in Malaysian Online Distance Learning Institutions - Zahir Osman,; Loo , Sin Chun; Raemah Abdullah Hashim,; Norsiah Aminudin, (ASEAN Journal of Open and Distance Learning, 2019)
The purpose of this study is to investigate the mediating effect of organizational commitment on leadership style and employee performance relationships in Malaysian online distance learning higher institutions. To analyse the causal relationships among organisational commitment, leadership style and employee performance, the Structural Equation Model was adopted. The model utilises the Partial Least Square procedure on data collected from a survey that yielded 206 usable questionnaires. The results showed that leadership style enhances organisational commitment in Malaysian online distance learning higher institutions. It also revealed that organisational commitment mediates the relationship between leadership style and employee performance. It is vital to do the research utilising experimental design by using longitudinal data in Malaysian online distance learning higher institutions via vigorous measures. The findings suggest that the relationship between leadership style and employee performance may reside in the influence of organisational commitment on employee performance, and that organisational commitment plays a crucial role in the Malaysian online distance learning higher institutions. This research is one of the first known efforts to use the bootstrapping technique to test the significance of the mediation effect in Malaysian online distance learning higher institutions. (Abstract by authors)